(untitled) (American & British Studies Annual, 2023)
The paper addresses the narrative of mutual healing, grieving and resilience in Sigrid Nunez’s novel The Friend. The aim of the article is to determine whether in the presented narrative shared trauma among different species leads to improved resilience of humans and animals, as well as whether a shared experience of grieving and healing is beneficial for both sets of beings involved. An overview of the healing process in humans and animals which takes place after trauma is provided. Although based on a work of fiction, this paper seeks to be a contribution to the field of trauma studies, highlighting the benefits and therapeutic value of human-animal relations and reflecting approaches in fiction.